Eksistensi Tradisi Mbecek Pada Masyarakat Desa Temuguruh, Banyuwangi Dalam Pesta Pernikahan - Suaidin, Vivi; Agustin, Nadila Putri; Fania, Friska; Hasinul, Farhan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The mbecek tradition is a tradition passed down from generation to generation in the village of Tempuguruh, Banyuwangi. Mbecek is not an activity of attending a celebration by bringing souvenirs to give to the person having the celebration. With this tradition, the people of Tempuguruh village will make an effort to be present to fulfill the invitation that has been given. Usually they will bring donations in the form of money and basic necessities to help people who are having a celebration. Mbecek is not only for going to weddings, sometimes also for attending circumcision parties, thanksgivings and various other events. However, this research focuses on weddings. The traditional values contained in mbecek attracted the author's attention to research further into the existence of mbecek in Temuguruh village, Banyuwangi district. The value of social order is formed in this tradition, the temuguruh community will attend this celebration immediately because they comply with the norms that exist in social life. So like it or not, people will mbecek when they receive an invitation. The research method in this writing uses a qualitative method with a case study approach, so that researchers can explore the lives of the Tempuguruh village community in carrying out the Mbecek tradition. So that researchers get detailed information to find out the existence of the mbecek tradition that exists among the people of Temuguruh Village.